2021
DOI: 10.3390/app11031106
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Coastal Geodynamic Processes on the Distribution of Trace Metal Content in Sandy Beach Sediments, South-Eastern Baltic Sea Coast (Lithuania)

Abstract: Sandy coasts are one of the most dynamic spheres; continuously changing due to natural processes (severe weather and rising water levels) and human activities (coastal protection or port construction). Coastal geodynamic processes lead to beach sediment erosion or accumulation. The coast’s dynamic tendencies determine the changes in the volume of beach sediments; grain size; mineralogical; and geochemical composition of sediments. In addition to lithological and mineralogical analysis of sediments, geochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…The amount of cadmium in the analysed area was approximately 0.003 mg•kg -1 . Similar dependencies were also obtained for the beaches at the Baltic Sea, where it was evidenced that cadmium contents in sandy soil are relatively low, but can increase in the vicinity of an industrial or port zone (Karloniene et al, 2021). Research conducted in beaches of south Spain showed the content of cadmium in sand higher in the vicinity of a petroleum refinery, potentially leading to the pollution of marine waters, and posing a threat for the public health (Nelson et al, 1993).…”
Section: Discussionsupporting
confidence: 60%
“…The amount of cadmium in the analysed area was approximately 0.003 mg•kg -1 . Similar dependencies were also obtained for the beaches at the Baltic Sea, where it was evidenced that cadmium contents in sandy soil are relatively low, but can increase in the vicinity of an industrial or port zone (Karloniene et al, 2021). Research conducted in beaches of south Spain showed the content of cadmium in sand higher in the vicinity of a petroleum refinery, potentially leading to the pollution of marine waters, and posing a threat for the public health (Nelson et al, 1993).…”
Section: Discussionsupporting
confidence: 60%
“…These coarser particles are deposited on the beach as well as in the nearshore zone. The finer‐grained light mineral particles in the swash zone are typically washed away and the heavier parts of the fine‐grained sediment fractions (i.e., the heavy minerals) are deposited with the coarser fractions (Karlonienė et al, 2021). Therefore, the high HREE, TiO 2 , Fe 2 O 3 T, Zr, Th, Y, Ni, Pb and Cr concentrations in the shoreline sediments indicate that their abundances are likely connected to the hydrodynamic conditions of the coast.…”
Section: Discussionmentioning
confidence: 99%
“…Coastal processesGeodynamic processes in coastal regions can lead to variations in the grain size, mineralogical composition, and geochemical pattern of beach/ shoreline sediments(Karlonienė, Pupienis, Jarmalavičius, Dubikaltinienė, & Žilinskas, 2021); conversely, the grain-size pattern and provenance of sediments can directly influence the geochemistry of shoreline sandy sediments. Few Sonadia Island samples contained high relative abundances of Al 2 O 3 , Fe 2 O 3 T, TiO 2 , P 2 O 5 , Zr, Ni, Cr and V, because of the presence of clay materials as well as hydrodynamic sorting effects along the seashore Garzanti et al (2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Karlonien ė et al [12] assessed trace heavy metals' temporal and spatial distribution in the sandy beach sediments along the south-eastern Baltic Sea coast (Lithuania). They studied how geochemical analysis can provide valuable information about the local and regional patterns of sediment transport, distribution, provenance, and coasts condition.…”
Section: Dynamics Of the Sedimentsmentioning
confidence: 99%